2009
DOI: 10.1111/j.1468-3083.2009.03186.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of solitary oral pigmented lesions: a prospective study

Abstract: Solitary pigmented lesions are uncommon in the oral mucosa. A review of the literature reveals no information regarding the relative frequency of these lesions. The purpose of this study is to determine the relative prevalence of solitary oral pigmented lesions in a selected population of patients. This study includes 265 consecutive patients who accessed the dermatology out-patients' surgery of the Department of Dermatology, University of Florence between March 2006 and July 2007. The sample we studied presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 7 publications
8
16
0
2
Order By: Relevance
“…The literature is replete with studies about prevalence of oral mucosal lesions in different populations from both developed and developing countries . However, only a few studies specifically examined the relative frequency of pigmented oral lesions . For example, De Giorgi et al ., reported that the prevalence of solitary pigmented oral lesions in patients attending a dermatology center in Italy as 5.7%.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is replete with studies about prevalence of oral mucosal lesions in different populations from both developed and developing countries . However, only a few studies specifically examined the relative frequency of pigmented oral lesions . For example, De Giorgi et al ., reported that the prevalence of solitary pigmented oral lesions in patients attending a dermatology center in Italy as 5.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Yüzeyel lamina propriada melanin inkontinensi sık görülen bir durumdur. Mukozal pigmentasyonun rengi, mukozadaki pigmentin derinliğine bağlı olarak kahverengiden maviye veya siyaha değişen renk tonlarından birisi şeklinde görülmektedir (Tyndall etkisi) [1][2][3] . Oral pigmente lezyonların tanısı, genelde klinik muayene ve hastadan alınan öykü ile konulmaktadır.…”
Section: Gi Riflunclassified
“…Kronik inflamasyon ya da travmaya bağlı, postinflamatuar pigmentasyon görülebilir. Sigara kullanımı ve bazı sistemik ilaçlar da oral pigmentasyona neden olabilir [1][2][3][4] . Bu derlemede en sık oral pigmentasyona neden olarak antiteler, klinik ve ayırıcı tanıları gözönünde bulundurularak sunulmaktadır.…”
Section: Gi Riflunclassified
“…The deposition of coloring matter, coloration, or discoloration by a pigment pertaining to the gingiva is called gingival pigmentation 1 . The lesions may be solitary, multiple, or diffuse 2 . Exogenous or endogenous factors are implicated in the etiology of oral pigmentation 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The lesions may be solitary, multiple, or diffuse 2 . Exogenous or endogenous factors are implicated in the etiology of oral pigmentation 2,3 . Pigmentation caused by exogenous factors, such as embedded foreign material, amalgam from dental restorations, or pencil lead, is called an “oral tattoo.”…”
Section: Introductionmentioning
confidence: 99%